PROBLEMS WITH THE LAW ON PRAYING AN INVISIBLE ECLIPSE FROM THE PERSPECTIVE OF ISLAMIC ASTRONOMY - Arisafitri, Novi; Ramadhan, Rizal; Alam, Bahrul (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2023)
Solar and lunar eclipses are natural phenomena that occur two to three times each year. All Muslims are advised to perform the sunnah eclipse prayer when an eclipse occurs. However, the eclipse phenomenon cannot always be seen directly from Earth due to weather conditions that prevent the eclipse phenomenon of the Sun or Moon from being seen. The purpose of this study is to determine the law of eclipse prayer when it is not visible. The research methodology employed is qualitative library research, which involved the extraction of data from the Nash Al-Qur'an and Hadith, as well as the analysis of the opinions of scholars. The findings indicate that if an eclipse occurs and is subsequently obscured by clouds, dust, or other obstructions, the eclipse prayer should be performed upon the knowledge that an eclipse has occurred. This condition is still considered an eclipse as long as the individual believes that the eclipse will be completed at a specific time. In the event that the eclipse is visible with thin clouds or a clear or cloudy sky and then hesitates, it is advisable to wait until the eclipse is confirmed to have occurred before commencing the prayer. Conversely, if the eclipse is not visible due to cloud cover or otherwise, despite the existence of information indicating the occurrence of an eclipse, the recommendation to pray the eclipse remains invalid.